2014
DOI: 10.5430/ijba.v5n6p77
|View full text |Cite
|
Sign up to set email alerts
|

Adoption of Technology as a Response Strategy to Globalization: A Study of Manufacturing Firms in Kenya

Abstract: Globalization affects local and international firms in many ways. Studies have shown that factors in the internal as well as external environments of firms influence the rate to which globalization will affect them. On the local scene however, no known studies have been done on the response of manufacturing firms to counter globalization. In addition, since the concept of globalization is multidimensional and its influence is varied in nature, this study aimed at investigating how manufacturing firms in Kenya … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…In Kenya there has been low organization commitment and turnover of the workforce has been high because of low entry and exit barriers in the industry (IRA., 2013). Graham (2008) cited in (Kinyanjui, 2015) studied the internal operational procedures in the Kenyan insurance industry as compared to the Greek insurance industry which included Human resource procedures concluded that there is wide spread dissatisfaction both internally and externally stemming from the insurances failure to satisfy customers and employees alike. Thus, the growth of insurance industry in Kenya is lower than the country's average economic growth (Lang'at, 2018).…”
Section: According Tomentioning
confidence: 99%
See 1 more Smart Citation
“…In Kenya there has been low organization commitment and turnover of the workforce has been high because of low entry and exit barriers in the industry (IRA., 2013). Graham (2008) cited in (Kinyanjui, 2015) studied the internal operational procedures in the Kenyan insurance industry as compared to the Greek insurance industry which included Human resource procedures concluded that there is wide spread dissatisfaction both internally and externally stemming from the insurances failure to satisfy customers and employees alike. Thus, the growth of insurance industry in Kenya is lower than the country's average economic growth (Lang'at, 2018).…”
Section: According Tomentioning
confidence: 99%
“…In this regard the Insurance Industry in Kenya continues to face performance challenges with low penetration at 3% according to IRA, report 2017 as compared to other industries as well as reduced profit margins (Azinga, Kamaara, & Ombui, 2020). Okiko (2014), Kinyanjui (2015) opines that the insurance industry in Kenya faces a high rate of staff turnover. High employee turnover due to low organizational commitment has been argued to be the key blockage to the companies' ability to steer their penetration and performance.…”
Section: Statement Of the Problemmentioning
confidence: 99%